Finite-Difference-Time-Domain (FDTD) Algorithm for Multiblock Grids - Hahn, Ingo; Kräck, Veronika (ICEM 2014, 2014)
In this paper, a finite-difference time-domain (FDTD) algorithm for multiblock grids is presented to solve electromagnetic field problems. In order to compute the magnetic field distribution in the presence of complex geometries, multiblock grids are used instead of conventional cartesian single-block grids for discretization. Those multiblock grids are globally unstructured, but locally structured. For the implementation of such grids the exchange of information across block interfaces is essential. Simulations of electromagnetic field problems using the multiblock FDTD formulation demonstrate the validity of the method.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.finite
Keywords: block communication; finite-difference time-domain (FDTD) method; multiblock grid; multiblock solver